‘Tell me about the time you remember the best’: the effect of a remember best prompt on adults’ reports of a repeated emotionally stressful event - Dilevski, Natali (Psychology, crime & law, 2023)
In two experiments we investigated the effect of a ‘remember best’ prompt on recall of one instance of a repeated event. Adult female participants (N = 98 Experiment 1; N = 100 Experiment 2) engaged in imagined experiences of abusive relationship encounters on either one occasion (single group) or four occasions (repeat-last and repeat-best groups). Participants then completed a memory assessment for the target instance. In the single and repeat-last groups, participants recalled a pre-determined target instance (i.e. last instance for repeat-last group), while the repeat-best group self-selected which instance to discuss (i.e. the time they ‘remember best’). In Experiment 1, repeat-best participants selected an instance based on when it occurred, while in Experiment 2, participants identified and uniquely labelled the instance remembered best. Experiment 1 results revealed that the ‘remember best’ prompt was not effective in enhancing accurate retrieval of one instance, while the ‘remember best’ prompt in Experiment 2 did appear to enhance retrieval when compared to the control groups. These findings suggest that accurate retrieval of one instance of a repeated event might depend on how memory is cued. The forensic implications of these findings for testimonies of repeated abuse (e.g. domestic abuse) are discussed.